The implications of ICT adoption in the Malaysian civil courts: with special reference to the legal position in England and Wales / Ani Munirah Mohamad - Mohamad, Ani Munirah (Institute of Graduate Studies, UiTM, 2017)
The ICT adoption in the Malaysian courts has been problematic and raises several implications, involving both legal and non-legal ones, such as technical, organisational and social. Previous research in Malaysia had not addressed the said implications. Within this context, the central arguments of this research are two-folds: firstly, the implementation of ICT in the Malaysian courts has impacted not only on the users and courts but also raises a variety of legal, technical, organisational and social implications. Secondly, the lack of legal sanctions to most of the existing ICT applications in the Malaysian courts suggests that law will eventually lag far behind technology and will remain so in the near future. Guided by this thesis, this study aims at examining the implications of ICT adoption in the Malaysian courts on the users and the courts; the implications of the ICT adoption on the laws in Malaysia as compared to that in England and Wales; the theories of unified acceptance and use of technology and risks perception in informing the research; and to propose for the strengthening and improving the delivery of the justice system in the Malaysian civil courts through ICT adoption. Adopting a qualitative research, this study engaged both the primary data obtained from five case studies and the secondary data obtained using the doctrinal approach. The evidence from the research is extensively reported in Chapter Five…